Evolving landscape of female cancers along with attributable risk factors in China from 1990 to 2021, and projections to 2040 - Han, Yali; Chen, Hui; Song, Didi; Li, Rongrong; Zhang, Tongchao; Yang, Xiaorong (Frontiers in Public Health, 2025)
BackgroundFemale cancers pose a significant health burden in China, and this study identified and projected epidemiological trends of these cancers.MethodsWe extracted incidence, prevalence, mortality, and disability-adjusted life-years (DALYs) data of female breast, cervical, uterine, and ovarian cancers in China from the Global Burden of Disease (GBD) Study 2021. The estimated annual percentage change (EAPC) and the age-period-cohort (APC) model were used to explore the trends, and the Bayesian APC model (BAPC) was employed to project the burden.ResultsIn 2021, breast cancer had the highest incidence (38.58 × 104) and mortality (8.81 × 104) cases, with the age-standardized rates of incidence (ASIR) and prevalence (ASPR) doubling from 1990 to 2021 (EAPC: 2.34 and 2.49). However, the age-standardized rates of mortality (ASMR) and DALYs (ASDR) declined slightly (EAPC: −0.62 and −0.52). Cervical cancer saw a slight increase in ASIR (EAPC: 0.88), a substantial increase in ASPR (EAPC: 2.50), but decreases in ASMR and ASDR (EAPC: −1.05 and −1.07). Uterine and ovarian cancers had slight ASPR increases and moderate ASMR/ASDR declines. High red meat consumption was the leading risk factor for breast cancer, and unsafe sex practices accounted for nearly all cervical cancer DALYs. High BMI contributed to a growing proportion of breast, uterine, and ovarian cancers. Projections indicated increasing burdens for breast, uterine, and ovarian cancers by 2040, with cervical cancer declining.ConclusionThe female cancer burden in China has been rising and will continue to do so. Targeted prevention and intervention strategies are crucial.